Gaining Entrée into a Micronesian Islander-Based Community Organization Through Culturally Responsive Team Building and Reflection - S. Robert Spence Jr; Jacqueline Leung; Shelley Geil; Connie K. Y. Nguyen-Truong (JMIR Publications, 2020)
Building trust and rapport is crucial in developing sustainable relationships with communities of color who have suffered historical trauma (Nguyen- Truong, Closner, & Fritz, 2019; 1Nguyen-Truong, 1Leung, & Micky, 2020a). A history of nuclear weapons testing by the United States in Micronesia, and subsequent ill-prepared cleanup efforts, has created a historical trauma for the Micronesian Islander community (Letman, 2013). The purpose of this brief article is to describe a critical foundational engagement project approach when gaining entrée into a Micronesian Islander community-based organization to co-develop the culturally relevant main project to improve rates of Micronesian Islander enrollment in early childhood learning (ECL) programs. Building a sustainable community-academic partnership through culturally responsive team (CRT) building and leveraging the collective strengths, to address a community need, took half a year for relationship building, and shared decision-making.